Efektifitas Bahan Ajar Buku Panduan Pembelajaran Kebencanaan Kabupaten Klaten Dengan Teori Pembanding Penyusunan Modul Bahan Ajar Pada Bencana Gempa Bumi Melalui Strategi Team Game Tournament Dan Snow Balling Di Sma Negeri 2 Klaten - Jannah, Azhari Miftakhul; , Dr. Tjipto Subadi, M.Si (2017)
The research objective to determine 1) the teaching terials book Klaten district instructional guides with earthquakes material is appropriate or not compare to guide thevelopment of teaching materials. 2) to find out how much difference the earthquake disaster knowledge value through a strategy of Team Game Tournament and and Snow Balling in SMA Negeri 2 Klaten. This type of research is experimental study, the experimental study has several designs, where this research using the Pre-Experiment Desaign. This study design shape wear One-Gruop pretest-posttest design, then in this design are pretest, before being treated or action. The results of the treatment can be seen more clearly and accurately, it can compare the situation before being treated. The method used was experimental study using two experimental class by comparing the learning outcomes of students who are both given the carrying different. Classes are used as an experimental class I was in class XI IPS 1 totaling 38 students with the learning process using a strategy of Snow Balling and grade used for experiments II is class XI IPS 2 by the number of students 37 students in the learning process using a strategy of Team Game Tournament. The data analysis technique used is paired t_Test to determine differences in student learning outcomes in both the experimental class. Based on the results of analysis show that the experimental class I with Snow Balling method of obtaining the average value of 42.28 pretest and posttest average value of 56.85 by showing an increase of 15%. While the value of the experimental class II using Team Game Tournament gain average value of 40.09 pretest and posttest average value of 70.60 with the figures show an increase of 30%. With the results of the acquisition value of these students can be concluded that the use of teaching materials guide books disaster can be considered effective because it can improve learning outcomes using cooperative learning methods Team Game Tournament rather than using strategies Snow Balling